Maximizing Prospective Students through Instagram-Driven Influence Maximization for University Branding - Ma'ady, Mochamad Nizar Palefi; Hidayat, Alifiansyah Arrizqy; Nasution, Anita Hakim; Kusumawati, Aris; Insani, Rokhmatul (Society of Visual Informatics, 2025)
In many developing countries, private universities face considerable financial challenges due to their limited sources of income. Unlike public universities, which receive substantial government subsidies, private institutions must rely primarily on tuition fees and student enrollment to sustain their operations. This financial dependency pushes private universities, particularly in Indonesia, to invest heavily in branding and marketing to attract prospective students. Social media platforms, especially Instagram, have emerged as crucial tools in these efforts. Instagram enables universities to engage with potential students directly, providing a space for showcasing academic programs, campus life, and student achievements. This paper’s goal is to explore the potential of Instagram-driven influence maximization (IM) techniques for enhancing university branding. Traditionally, these techniques are employed in product marketing to increase consumer engagement and sales, but their application in higher education remains relatively unexplored. We aim to address this gap by examining three promising IM methods that private universities can adopt: first, leveraging Instagram’s broadcast channel feature to communicate effectively with large audiences in real time; second, selecting key opinion leaders (KOLs) from influencer marketplace platforms to enhance credibility and broaden outreach; and third, optimizing the use of targeted hashtags to increase discoverability and engagement. As a result, we provide a review of recent evidence supporting the effectiveness of these strategies in higher education marketing. By adopting these techniques, private universities can improve their digital presence, enhance brand awareness, and increase student enrollment. IM with uncertainty is a challenging educational landscape for future research.